Structural change, growth and inequality : implications for poverty alleviation in Nigeria - Na'iya, Isma'eel Ibrahim (Kulliyyah of Economics & Management Sciences, International Islamic University Malaysia, 2012)
During the last few decades studies on long-run economic growth and development are quite numerous. Most of these studies conducted in the industrialized as well as the newly emerging economies like those of East Asian miracle economies confirm Kuznets' hypothesis that the agricultural sector dominates at the early stage of growth. This situation changes as the economy's growth momentum proceeds due to rising productivity in agricultural and manufacturing sectors as a result of improvement in technology and human capital. During the process of structural change based on inclusive growth the economically active labour force must be absorbed in better paid jobs and sectors. This gives rise to increase in income of individuals and households leading to improvement in welfare and reduction in poverty incidence. As the rise in growth is sustained, the services sector takes over as the leading sector in the economy contributing more to GDP and providing more employment. This is because as income increases individuals and households devote more of their income to services which are in most cases labour intensive and income elastic in nature. This process of economic growth is referred to as structural transformation. As observed in many countries, a smooth and well balanced structural transformation leads to a very significant improvement in overall welfare, improved income distribution and sustained poverty reduction. However, given the importance of structural transformation in the development process and its relevance to poverty reduction the studies on economic growth and inequality during the process of structural transformation are rather scanty in Nigeria. This thesis aimed at filling this gap. The study uses both descriptive and empirical analysis to examine the interrelationship among the relevant variables. Beside using the OLS to test the strength of association, the bound testing technique based on the Autoregressive Distributed Lag (ARDL) is used to examine the long-run relationships among four variables (poverty, structural change, economic growth, and inequality). The Johansen and Juselius approach to cointegration is also used to investigate the sectors that contribute most to poverty reduction in the country. The study finds that although Nigerian economy has benefitted from all the oil windfalls, it had not been able to make use of the opportunities to address the issue of poverty and inequality. This has been blamed on the lack of good governance and economic mismanagement that emanated due to rent-seeking activities of politicians and government officials thereby making the economy vulnerable to “Dutch Disease”. Therefore, poverty remained endemic in the country despite the huge amounts of revenues generated from sales of oil. Poverty alleviation policies and programmes, implemented over the years, were ineffective due to poor implementation, endemic corruption and mismanagement. It is found that despite very low rate of structural change in Nigeria, there exists long-run relationship among the variables in the study. The insignificance of the structural change variable in the first model confirms our earlier findings on slow trend of structural transformation. It also confirms the claims that lack of effective and pro-poor structural transformation is one of the major development issues facing the country. Inequality reduction is found to be the major driving force in reducing poverty in Nigeria. It has been observed that there is a wide gap between the rich and the poor and among the states and the regions in the country not only in terms of incomes but also in terms of socioeconomic and political opportunities manifest through the distribution of both economic and intellectual power resources. Poverty incidence appears to be the highest in the Northern zones where human development encompassing education & health is the lowest. Hence, improvement in the distribution of economic and intellectual power